Pemanfaatan Bunker Jepang di Batu Bara Kecamatan Pesisir Lima Puluh, Kabupaten Batu Bara, Sumatera Utara sebagai Media Pembelajaran Sejarah - Hutapea, Dewi Margareta; Putri, Dita Marcellia; Safitri, Rahma Dina; Maulana, Rizki; Azhari, Ichwan (Innovative: Journal Of Social Science Research, 2025)
The bunker remnants from the Japanese occupation in Batu Bara represent a historical site that holds various educational and cultural values. This research aims to examine the role of the bunker as an effective medium for historical learning for students. The primary focus of this study is to explore the potential of the bunker as a learning medium that can enrich students' educational experiences. Through a qualitative approach, the research gathers data from literature reviews related to the history of the Japanese occupation in Indonesia. The findings indicate that the bunker not only serves as a silent witness to the past but also has the potential to become an interactive and engaging learning medium. The results show that the bunker can enhance students' awareness of the importance of cultural heritage and local history. Moreover, utilizing the bunker as a learning medium can increase students' motivation and interest in studying history, as well as develop their critical and analytical thinking skills. By leveraging the bunker as an educational tourist attraction, it is hoped that students' historical awareness will be heightened, fostering a sense of love for their homeland.